Iranian pediatric nurse's experience: The facilitators of the learning of ethical practices - Kobra Karami; Sadat SeyedBagher Maddah; Abbas Abbaszadeh; Farahnaz Mohammadi Shahboulaghi; Mohammadali Hosseini; Nazila MousaviArfa; Mohammad Almasian (Wolters Kluwer Medknow Publications, 2017)
Background: Ethical care is a core value in nursing. Pediatric nurses are in direct and continuous contact with children and their parents. They manage their lives and health. As part of the pediatric nurses' daily work, ethical issues play an important role in making decisions, are important to make decisions, and this capability is only achieved by ethical practice. This study aimed to explore the factors facilitating the learning of ethical practice among Iranian pediatric nurses. Materials and Methods: This study is a conventional qualitative content analysis based on the Graneheim and Lundman method. It was conducted through semi-structured interviews with two focus groups, incorporating 28 nurses working in pediatric wards. Unstructured observation and field notes were other methods of data collection. Purposive sampling continued until data saturation was ensured. All interviews were tape recorded and transcribed in verbatim. Results: Three main categories and 12 subcategories emerged from this study. The facilitating factors include (1) individual competencies (knowledge, experience, emotional intelligence, and loving children), (2) ethical imprinting (responsibility, reflection, empathy, and ethical beliefs), and (3) an environment that nurtures moral values (organizational, spiritual, family, and cultural environments) as facilitating factors. Conclusions: The promotion of nurses' competencies, ethical virtues, and imprinting, as well as improvement of the quality of nursing care must be the top priority of the health team. Undoubtedly, the success of the health care system is not possible without ensuring that pediatric nurses learn ethical practices.